Studi Pengelolaan Risiko dan Keselamatan Kerja pada Proyek Pembangunan Base Transceiver Station - Widyo Nugroho; Sulfiah Dwi Astarini; Eko Prihartanto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
The construction of Base Transceiver Stations plays a crucial role in expanding digital connectivity and supporting economic transformation; however, its implementation involves various risks ranging from technical and financial aspects to occupational safety. This study aims to identify, classify, and prioritize risks in Base Transceiver Station construction projects using the Analytical Hierarchy Process method, based on data obtained from literature reviews, interviews, and questionnaires. The analysis results indicate that physical risks carry the most significant weight, followed by design, economic, and natural disaster risks, with overall risk assessments ranging from moderate to high levels. The occupational safety analysis further reveals that the highest risks occur in foundation works, tower structure erection, fabrication, and electrical installation, where human resources and work methods are the dominant contributors to potential accidents. Therefore, the success of Base Transceiver Station construction projects is highly determined by the effectiveness of managing physical risks and the consistent implementation of occupational safety standards, ensuring that project objectives in terms of time, cost, and quality can be achieved while safeguarding worker safety